PENGARUH PERLAKUAN PELAPISAN UJUNG TERHADAP PENGURAN GAN PECAH PADA PATUNG KA YU (BAGIAN I) - Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1994)
Physical deformation such as checks or cracks is commonly encountered in the process of drying wood statues.  In the senses of economic and quality improvement, such a case has long been a serious handicap to the Balinese crofters.  A number of trials have been made through modification of drying schedules, but these gave  little protection agents check/crack development, particularly for the medium  to  large size  statues. The  use of polyethylene glycol  (PEG-1000) has significantly  reduced  the  rate  of physical deformation, however, it raised another problem  in finishing and could promote a surface  discoloration. This study  examined another approach of cracking prevention by application of coating treatments to the end grain of wood structure.Fresh  logs of  two  wood species,  i.e., sengon  (Paraserianthes  falcataria  {L.)  Nielsen.)  and  mindi  (Melia azedarach  L.)  were crosscut to 50 cm long specimens,  and then shaped into a simple cat-form statues sizing of approximately  21 cm  wide and 46 cm long. End coatings were applied separately using 4 different materials, i.e., resorcinol formaldehyde, polyvinyl acetate, wood filler and cement.  All treatments were accomplished approximately 30 minutes prior to oven drying, Physical deformation of wood statues was de/ermined  by measuring the width,  length and gap-size of cracks using a digital caliper. The related physical characteristics, such as moisture content and specific: gravity of each species were also determined.Sengon  had a lower  specific: gravity, but a  greater  green  moisture  content  and  dry-ability  than  mindi. Wood physical deformation of both treated and untreated sengon was obviously greater than mindi.   The effectiveness of end coating treatments in reducing  wood cracks  varied according  to  wood species  and the coating materials.     Wood statues  of sengon  experienced more rigorous cracks than those of mindi.   The  use of wood adhesives as coating materials gave a helter cracking protection than the wood filling agents. Although polyvinyl acetate could not greatly minimize the physical deformation  of belalu,  it revealed  to be the most effective coating material for cracking prevention.